Collaborative Learning Method in Teaching English - Martha Kumala; Thomas Pandonge (Sintuwu Maroso Journal of English Teaching, 2017)
The aims of this research are: (1) to describe the teaching learning process using Collaborative Learning Method at the Eight Grade Students of SMP Neg. I Poso Kota Selatan; (2) to describe the result of the teaching learning process using Collaborative learning Method at the Eight Class Grade Students of SMP Neg. I Poso Kota Selatan. The researcher uses qualitative descriptive design. The researchers chose eight grade students as the sample. The data were collected by classroom observation, interview, test and documentation to find out the using Collaborative Learning Method in teaching English. The result of the research showed that in the learning process the students are interested in using this method because they can communicate each other easily. Besides, they can help each other in the learning difficulties materials, as can be seen by the result of test.Keywords: Collaborative learning, teaching English